Implementasi Pembelajaran Pendidikan Agama Islam bagi Anak Berkebutuhan Khusus di Sekolah Luar Biasa Negeri 3 Lombok Timur - Muhammad Syukri; H. Jamaluddin; Muh. Azkar (PALAPA, 2023)
This have a look at ambitions to describe (explain) the implementation of Islamic non secular training getting to know for youngsters with unique wishes withinside the tremendous faculties of Negeri three East Lombok, beginning from making plans, enforcing and evaluating.This studies makes use of a descriptive qualitative approach. The techniques of facts series are observation, interview and documentation. The facts evaluation approach makes use of an interactive evaluation version that consists of 4 components, specifically facts series, facts reduction, facts presentation and end drawing. Checking the wetness of the facts makes use of criteria, specifically the extension of participation and triangulation of reassets and triangulation of techniques.The conclusions of this have a look at are 1) getting to know making plans for deaf and tough of listening to youngsters, studying powerful days, compiling a syllabus, compiling a Learning Program Plan and undertaking assessments, instructors are greater involved with the supply of coaching aids as a medium withinside the getting to know process; 2) the implementation of getting to know for the deaf the use of the maternal reflective approach (MMR) which includes conversation, visualization and making deposits, at the same time as the deaf use the Individual getting to know approach and the rhythmic motion approach; three) assessment of the getting to know effects of Islamic non secular training for deaf and tough of listening to youngsters with written tests, observations, and hands-on practice/action.